A Study of the Occurrence of Resonance under the Influence of Dynamic Forces on the Structural Elements of Electrical Installations - Y. V. Potachits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The increase in the levels of short-circuit currents in the power system of the Republic of Belarus requires the study of the parameters of the electrodynamic stability of the main structural elements of electrical installations with flexible conductors. In case of a short circuit in the network, currents tenfold exceeding the rated one hundreds of times can flow through the current-carrying part of the device. When the magnetic fields formed by these currents interact, significant electromagnetic forces arise, which have a destructive effect both on the current-carrying parts themselves and on the structural elements of electrical installations, viz. support insulators, switching devices, measuring equipment. The movement of the wires in a short-circuit mode leads to the appearance of significant dynamic loads in them, which, in turn, are transmitted to the portals, support insulators and electrical devices. A topical problem is the occurrence of unacceptable mechanical forces in the main structural elements that can cause their destruction. Thus, the analysis of the physical and mechanical parameters and geometric dimensions of the flexible busbar of switchgear shows that a violation of the condition of electrodynamic resistance to tension is unlikely due to the high mechanical strength of the large-section steel-aluminum wires used. At the same time, span-limiting portals, support insulators and other electrical devices have significantly lower permissible bending loads. When exposed to dynamic forces, the conductors bend and transfer the load to the structural elements which have certain elasticity. Thus, a reliable determination of dynamic loads, taking into account the current-carrying parts acting on the supporting structures, is possible only if a dynamic task is set. The article describes the methods of mathematical modeling and computational experiment for analyzing the parameters of the electro-dynamic stability of the main structural elements which are determined using coefficients that depend on the natural frequencies of oscillations and the nature of changes in dynamic forces over time. To solve these problems, mathematical models are compiled and boundary value problems are formulated for calculating the electrodynamic stability of structural elements, taking into account the possible coincidence of the frequencies of natural and forced oscillations of structural elements taking into account the probable coincidence of the frequencies of forced and natural vibrations of structural elements.